2014
DOI: 10.3168/jds.2013-6961
|View full text |Cite
|
Sign up to set email alerts
|

Mammary blood flow and metabolic activity are linked by a feedback mechanism involving nitric oxide synthesis

Abstract: To test which, if any, of the major milk precursors can elicit a rapid change in the rate of mammary blood flow (MBF) and to define the time course and magnitude of such changes, 4 lactating cows were infused with glucose, amino acids, or triacylglycerol into the external iliac artery feeding one udder half while iliac plasma flow (IPF) was monitored continuously by dye dilution. Adenosine and saline were infused as positive and negative controls, respectively, and insulin was infused to characterize the respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 38 publications
(58 reference statements)
2
24
1
Order By: Relevance
“…Both NO and polyamines play critical roles in mammary angiogenesis, milk production and consequent growth of the litter. Enhanced synthesis of NO from Arg may mediate increased mammary blood flow, thereby increasing nutrient delivery for milk production (Meininger and Wu 2002;Kim and Wu 2009;Cieslar et al 2014). Increased plasma NO concentration at d 21 of lactation from Arg supplementation at d 21 of lactation was consistent with this but it was impractical to measure blood flow in the present study.…”
Section: Discussionsupporting
confidence: 70%
“…Both NO and polyamines play critical roles in mammary angiogenesis, milk production and consequent growth of the litter. Enhanced synthesis of NO from Arg may mediate increased mammary blood flow, thereby increasing nutrient delivery for milk production (Meininger and Wu 2002;Kim and Wu 2009;Cieslar et al 2014). Increased plasma NO concentration at d 21 of lactation from Arg supplementation at d 21 of lactation was consistent with this but it was impractical to measure blood flow in the present study.…”
Section: Discussionsupporting
confidence: 70%
“…This decrease was consistent with the decreased supply of AA (particularly EAA) and mammary uptake in these animals. Thus, it appears that when a high dosage of glucose was given, AA availability to the MG was inhibited, and may have mainly resulted from a trend of decreased MPF in these animals observed in both our previous study [5] and another study [34]. In addition, our previous study showed that high dosage of glucose resulted in acute glycolysis in mammary epithelial cells (MEC), accumulated reactive oxygen species and decreased the antioxidant capacity of MEC [5].…”
Section: Effects Of Lmgs On Mammary Aa Utilizationmentioning
confidence: 63%
“…In the short term, mammary blood flow is positively regulated by nitric oxide through a feedback signal from adenosine, which indicates a decrease in cellular energy, and is negatively regulated by glucose [61]. On the other hand, longer-term glucose or starch infusion increased mammary blood flow [34,62,63].…”
Section: Endocrine Regulation Of Mammary Blood Flowmentioning
confidence: 99%